Современные подходы к лечению анемии у больных со злокачественными новообразованиями - Бессмельцев, С.С. (Iнститут експериментальної патології, онкології і радіобіології ім. Р. Є. Кавецького, 2008)
The importance of hemoglobin levels in determining the quality of life of cancer patients receiving chemotherapy has become increasingly clear both from randomized studies. It was first approved for the treatment of anemia in patients with chronic renal disease. Before recombinant human erythropoietin (rEPO) erythropoietin was available, blood transfusion was the only treatment option for severe cancer-related anemia. Potential complications associated with blood transfusion are transmission of infectious diseases, transfusion reactions, alloimmunization, over-transfusion and immune modulation with possible adverse effects on tumor growth. It is performed the analyses of effectiveness of rEPO therapy in any hematological malignancies and cancer patients and shown predictors efficiency of this therapy. To update the American Society of Hematology/American Society of Clinical Oncology (ASH/ASCO, 2007) recommendations for the use of rEPO.